Global Aerospace Monitoring and Disaster Management - Menshikov, Valery A. (Springer Vienna : Imprint: Springer, 2012)
In this book, space systems are situated in the global processes of the 21st century’s information society and the role that space information systems could play in risk management is determined; methods of detecting and forecasting of both natural disasters and technogenic catastrophes and existing global and regional monitoring systems are described; and the IGMASS is introduced with its architecture and design concept and social and economic aspects and estimates of its creation, development, and utilization. Finally, results of the international symposium held in Limassol, Cyprus, in November 2009 in preparation of the IGMASS project’s submission to the United Nations are discussed.